2015
DOI: 10.1007/s11426-014-5219-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in plasmonic organic photovoltaics

Abstract: Light trapping based on the localized surface-plasmon resonance (LSPR) effect of metallic nanostructures is a promising strategy to improve the device performance of organic solar cells (OSCs). We review recent advances in plasmonic-enhanced OPVs with solution-processed metallic nanoparticles (NPs). The different types of metallic NPs (sizes, shapes, and hybrids), incorporation positions, and NPs with tunable resonance wavelengths toward broadband enhancement are systematically summarized to give a guideline f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 62 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…What is more, the extremely large absorption cross sections of plasmonic NPs can capture light more efficiently than other optical materials [10]. These potential advantages make plasmonic NPs an ideal candidate for harnessing solar energy [11][12][13][14]. Jang et al [15] have reported that shape-controlled gold NPs on wide bandgap semiconductors can improve water-splitting photoactivity; they found that plasmonic octahedral gold NPs could be maximized near electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the extremely large absorption cross sections of plasmonic NPs can capture light more efficiently than other optical materials [10]. These potential advantages make plasmonic NPs an ideal candidate for harnessing solar energy [11][12][13][14]. Jang et al [15] have reported that shape-controlled gold NPs on wide bandgap semiconductors can improve water-splitting photoactivity; they found that plasmonic octahedral gold NPs could be maximized near electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk heterojunction polymer solar cells (PSCs) have been considered as a promising approach for delivering renewable energy due to their advantages of low cost, solution processability, low weight, and mechanical flexibility. To date, a power conversion efficiency (PCE) of over 10% has been reached for PSCs thanks to the development of novel photovoltaic materials, morphology optimization, interface engineering, and innovation of device structures. …”
Section: Introductionmentioning
confidence: 99%
“…spherical, pyramids, thin plates with a triangular, and other shapes of various sizes, with tunable resonance wavelengths have recently been studied [92][93][94][95][96]. Effortless solution processed fabrication makes them considerably more adoptive to be employed in organic/Si HSCs [97,98]. Wet chemical synthesis process makes possible the huge manufacturing of pure metallic nanocrystals with various types, sizes, shapes and dispersal [99][100][101] which can be easily incorporated in organic/Si HSCs to benefit from its plasmonic effect [102][103][104][105][106].…”
Section: Metallic Nanostructures For Highly Efficient Plasmonic Organic/si Hscsmentioning
confidence: 99%